Oxidative stress and activation of enzymatic antioxidative defence mechanism in Tetraselmis chui - Norhayati Yusuf; Nurul Shafiqa Yusof; Malinna Jusoh; Hazlina Ahmad Zakeri; Nurfarha Muhamad Zalan (Penerbit Universiti Kebangsaan Malaysia, 2025)
Oxidative stress occurs when there is an imbalance between the production of reactive oxygen species (ROS) and an organism's ability to detoxify these harmful intermediates, posing a significant challenge for aquatic organisms, including microalgae. Tetraselmis chui has developed defence mechanisms to manage oxidative stress, ensuring its survival and functionality in various ecosystems. This study explores the interactions between the growth, oxidative stress markers and the activation of enzymatic antioxidative defence systems in T. chui after 8 days of incubation. T. chui was cultured in F2 media and subjected to variations in media strength (F/2, F, F/4 and F/8), sucrose concentrations (0 to 50 g/L), pH (5 to 9), and light intensities (0 to 600 lux). Growth was highest in full-strength media and improved with 40 g/L sucrose addition. Growth was largely unaffected by pH, except at pH 5, which reduced it, while higher light intensities boosted fresh and dry weights. Full-strength media led to significant MDA and H2 O2 accumulation, while F/2 media exhibited higher ion leakage. The absence of sucrose increased H2 O2 and ion leakage but lowered MDA, whereas higher sucrose concentrations raised MDA while reducing ion leakage. pH 7 stimulated MDA production, with H2 O2 concentrations largely unchanged except in controls. Cells grown in darkness showed elevated MDA and ion leakage but reduced H2 O2 . CAT and APX activities were significantly enhanced in F/8 media, while gPOD was highest in full-strength media. Sucrose-free media induced CAT and APX but reduced gPOD activity. All enzyme activities were most strongly induced at pH 9. Light intensity at 150 lux favoured CAT and gPOD, whereas APX was more active in dark conditions. These findings unveil the strategies employed by T. chui in response to oxidative stress, highlighting its ecological adaptability and contributing to its potential to produce antioxidants for various industrial applications.